Aberrant resting-state brain activity in Huntington's disease: A voxel-based meta-analysis - Zhang, Sirui; Lin, Junyu; Cheng, Yangfan; Hou, Yanbin; Shang, Huifang (Frontiers in Neurology, 2023)
Introduction Functional neuroimaging could provide abundant information of underling pathophysiological mechanisms of the clinical triad including motor, cognitive and psychiatric impairment in Huntington's Disease (HD). Methods We performed a voxel-based meta-analysis using anisotropic effect size-signed differential mapping (AES-SDM) method. Results 6 studies (78 symptomatic HD, 102 premanifest HD and 131 healthy controls) were included in total. Altered resting-state brain activity was primarily detected in the bilateral medial part of superior frontal gyrus, bilateral anterior cingulate/paracingulate gyrus, left insula, left striatum, right cortico-spinal projections area, right inferior temporal gyrus area, right thalamus, right cerebellum and right gyrus rectus area. Premanifest and symptomatic HD patients showed different alterative pattern in the subgroup analyses. Discussion The robust and consistent abnormalities in the specific brain regions identified in the current study could help to understand the pathophysiology of HD and explore reliable neuroimaging biomarkers for monitoring disease progression, or even predicting the onset of premanifest HD patients.